Penfigoide de membranas mucosas com estenose esofágica grave Mucous membrane pemphigoid with severe esophageal stricture - Lívia do Nascimento Barbosa; Roberto Souto da Silva; Gustavo Costa Verardino; Alexandre Carlos Gripp; Maria de Fátima Guimarães Scotelaro Alves (Sociedade Brasileira de Dermatologia, 2011)
O penfigoide de membranas mucosas é entidade nosológica encarada como um fenótipo, que engloba várias dermatoses autoimunes com lesões bolhosas subepidérmicas, ocorrendo predominantemente nas membranas mucosas, com êxito cicatricial. O acometimento esofágico no penfigoide de membranas mucosas é raro e observado em pacientes com lesão disseminada. As alterações mais comuns são múltiplas membranas ou constrições esofagianas. No presente relato, os autores apresentam paciente com PMM sem lesões cutâneas e estenose esofágica grave, que entrou em remissão após uso de imunoglobulina venosa Mucous membrane pemphigoid (MMP) is a rare nosological entity. MMP consists of a clinical phenotype in which several autoimmune subepidermal bullous diseases are classified. It occurs predominantly in the mucous membranes and usually results in scarring. Esophageal involvement in MMP is rare and is generally seen in patients in whom lesions are widespread. The most common alterations are multiple esophageal membranes or strictures. In the present case, the authors report on a patient with MMP without any skin lesions and with severe esophageal strictures who went into remission following use of intravenous immunoglobulin